Una Escala Psicométrica Breve para Evaluar el Estado Cognitivo de Hispanoparlantes de Edad Mayor - Sánchez-Ayéndez, Melba; Cabán, Carlos A.; Fernández, Leticia; Rosich, Walter; Dávila, Ana L.; Larriuz, María Celeste; Hernández, Johan; García-Guruxarri, Alberto; Palloni, Alberto (Puerto Rico Health Sciences Journal, 2011)
see manuscript